INFLUENCE OF THE METAL MATRIX STRUCTURE OF HIGH-DUTY CAST IRON ON COERCIVELY SENSITIVE MAGNETIC PARAMETER AND SPEED OF SOUND - S. G. Sandomirsky; V. L. Tsukerman (Литьë и металлургия)
The analysis of influence of changes in the structure of the metal base of high-duty cast ironcompact castings with a constant form of graphite inclusions on the coercive sensitive magnetic parameters and the speed of sound is held. The efficiency of joint use of the results of magnetic and ultrasonic measurements to control the shape of inclusions in the iron and pearlite content in its metallic matrix is shown.